Preparation and mechanical property of electrodeposited Al-graphene composite coating. (5th December 2016) - Li, Na; Zhang, Lan; Xu, Miting; Xia, Tian; Ruan, Xinwei; Song, Shan; Ma, Huizhong
Abstract: Al-graphene composites were successfully prepared from the organic solvent solution system of AlCl3 and LiAlH4 dissolved in tetrahydrofuran by electro-deposition technique to improve the mechanical properties of aluminum matrix. Both hardness and wear behaviors of coatings were investigated. Scanning electron microscopy (SEM), Energy spectrum analysis (EDS), X-ray diffraction analysis (XRD) and Raman spectrum were performed to characterize the morphology and structure of composites. The results indicated that graphene nanoplatelets (GNPs) distributed in the aluminum matrix were able to improve the hardness and antifriction properties of composites significantly. In comparison with pure aluminum coating, 3.8- fold increases in the hardness and 11-fold decreases in the friction coefficient of Al-graphene composite coatings are attributed to the remarkable mechanical strength and excellent self-lubrication of graphene. Graphical abstract: Highlights: The preparation of Al-graphene composite coatings by the technique of electro-deposition for the first time The sandwich structure formation of graphene nano-platelets wrapped by Al crystalline grain Investigation of hardness and antifriction properties Higher hardness and lower friction coefficient of Al-graphene composites than Al coating